PHENOMENON OF FANDOM WAR IN K-POP COMMUNITY ON SOCIAL MEDIA - Marcelino Letwory, Aldy; Sihombing, Lambok Hermanto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pembangunan Nasional Veteran Jakarta, 2023)
This research aims to discuss the phenomenon of fan wars between fans of a K-pop group and fans of other K-pop groups. Furthermore, it explores the reasons and purposes of this incident among K-pop fans, using the observation method based on Stuart Hall's Encoding-Decoding theory. This research will analyze several fan war cases that occurred some time ago. The results of this study indicate that the fan war phenomenon has several ways, like replying to each other's comments on social media using insulting and harsh words commonly known as flaming, making tweets that bring down idols from other fans, and making videos containing hoax news. The interference of toxic fans from each fandom is the reason this fan war can happen, and the selfish nature of each fan who wants to show their prowess to other fans is their main goal. Ultimately, this phenomenon is just a form of selfishness from every fan toward their idol.